Adaptation to Endophytic Lifestyle Through Genome Reduction by Kitasatospora sp. SUK42 - Zin, Noraziah M.; Ismail, Aishah; Mark, David R.; Westrop, Gareth; Schniete, Jana K.; Herron, Paul R. (Frontiers in Bioengineering and Biotechnology, 2021)
Endophytic actinobacteria offer great potential as a source of novel bioactive compounds as they can offer protective or growth promoting compounds to the plant in question. To investigate the potential for the production of secondary metabolites by endophytes, we recovered a filamentous microorgansism from internal tissue of the tree Antidesma neurocarpum Miq. Phenotypic analysis and whole genome sequencing revealed SUK42 to be a member of the actinobacterial genus Kitasatospora and represents the first entophytic bacterium sequenced from this genus. This strain has a small genome in comparison with other type strains of this genus and has lost metabolic pathways associated with Stress Response, Nitrogen Metabolism, and Secondary Metabolism. Despite this, SUK42 can grow well in a laboratory environment and encodes a core genome that is consistent with other members of the genus. Finally, in contrast to other members of Kitasatospora, SUK42 encodes saccharide secondary metabolite biosynthetic gene clusters, as well as a cluster with similarity to the acarviostatin cluster, the product of which displays α-amylase inhibitory activity. As extracts of the host plant demonstrate this inhibitory activity, it suggests that the endophytic partner might provide the potential medicinal properties of A. neurocarpum and illustrate the potential for exploitation of endophytes for clinical or industrial uses.